2016
DOI: 10.1530/jme-16-0025
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes, aldosterone and obesity-related hypertension

Abstract: Aldosterone and obesity a nguyen dinh cat and others 57:1 F7-F21 AbstractUnderstanding the mechanisms linking obesity with hypertension is important in the current obesity epidemic as it may improve therapeutic interventions. Plasma aldosterone levels are positively correlated with body mass index and weight loss in obese patients is reported to be accompanied by decreased aldosterone levels. This suggests a relationship between adipose tissue and the production/secretion of aldosterone. Aldosterone is synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 141 publications
0
29
0
Order By: Relevance
“…This presentation is partially associated with the activation of the RAAS pathway as a consequence of recurrent hypoxemia and hypercapnia while OSAS patients are asleep [7]. Additionally, obesity was common in patients with PA plus OSAS, as adipocytes and their derivative factors have been shown to activate the local RAAS pathway [18]. However, we did not find the AHI positively related to PRA as showed in the Di Murro’s study [3].…”
Section: Discussionmentioning
confidence: 64%
“…This presentation is partially associated with the activation of the RAAS pathway as a consequence of recurrent hypoxemia and hypercapnia while OSAS patients are asleep [7]. Additionally, obesity was common in patients with PA plus OSAS, as adipocytes and their derivative factors have been shown to activate the local RAAS pathway [18]. However, we did not find the AHI positively related to PRA as showed in the Di Murro’s study [3].…”
Section: Discussionmentioning
confidence: 64%
“…A novel pathway via which leptin may mediate hypertension in obese women is via activation of the aldosterone-mineralocorticoid receptor (MR) axis (Figure 1). Peripheral effects of MR activation outside of its role in renal sodium retention have been identified and linked with hypertension and vascular dysfunction in obesity in males and females 72, 73 . Aldosterone levels increase in correlation with adipose tissue and BMI moreso in females than in males 74 .…”
Section: Aldosterone May Be a Sex-discrepant Mechanism Implicated In mentioning
confidence: 99%
“…On the other hand, the activation of mineralocorticoid receptors can also induce the differentiation of preadipocytes to mature adipocytes via the induction of cytokines [ 27 ]. Adipocyte-derived factors which can influence adrenal aldosterone secretion include leptin, adiponectin and complement-C1q TNF-related protein-1 (CTRP-1) [ 28 ]. It has also been found that increased leptin signaling can enhance CYP11B2, inducing increased aldosterone synthesis and release [ 29 ].…”
Section: Discussionmentioning
confidence: 99%